Rhythmic Auditory Music Stimulation increases task-distraction during exercise among cardiac rehabilitation patients: A secondary analysis of a randomized controlled trial. (March 2021) - Nwebube, Chineze; Faulkner, Guy E.; Thaut, Michael H.; Bartel, Lee R.; Stukel, Therese A.; Redelmeier, Donald A.; Marzolini, Susan; Chen, Joyce L.; Goodman, Jack M.; Oh, Paul I.; Trainor, Laurel J.; Wolpert, Jeff; et al.
Abstract: Objective: The aim of this study was to determine the mechanisms by which Rhythmic Auditory Music Stimulation (RAMS) improves exercise among patients participating in cardiac rehabilitation. Methods: 168 English speaking patients over the age of 18 years, were recruited from the Cardiac Rehabilitation and Prevention Program. Participants were randomly assigned to one of three groups (n = 56 each) as part of a 12-week intervention: (1) RAMS (2) preference-based audiobooks, or (3) white noise or silence audio-controls. All participants received an iPod with the audio intervention to maintain blinding. Study outcomes included pace-deviation between actual vs. prescribed exercise, self-reported arousal, perceived exertion, task-attentiveness during exercise and perceptual experiences associated with the audio-content itself. Trial registry: Clinicaltrials. gov NCT02946060 . Results: An individual's actual exercise pace was highly correlated with their prescribed exercise pace, with no significant differences in pace deviation across interventions (P = 0.61). Patients randomized to RAMS or audiobooks reported significantly lower arousal scores during exercise (P = 0.01), lower exercise-attentiveness (P < 0.001), and modestly lower perceived exertion (P = 0.06) during exercise than did controls. Participants assigned to RAMS and audiobooks reported being more attentive to, and happy with, their overall audio-experiences during exercise than controls (P < 0.001). Conclusions: RAMS playlists and audiobooks induced a mood-enhancing task-distraction effect during exercise. Such findings may underscore the potential benefits of preference-based audio-content during exercise. Highlights: This is the first study to compare Rhythmic Auditory Music Stimulation (RAMS) to audiobooks, a preference-based control. RAMS had no effect on an individual's exercise pace, but lowered arousal and decreased attentiveness to the exercise task. These findings may also be applicable to other audio interventions that produce a positively distractive effect.